Alcohol consumption habits and their impact on academic performance: analysis of ethanol patterns among health students. a cross-sectional study - Brito, Ana Paula Amaral de; Lima, Aísa de Santana; Rocha, Átina Carneiro; Gonçalves, Beatriz Muniz; Freitas, Dalila Maria Costa Baraúna de; Oliveira, Gleice de Jesus; Lima, Jamily Kaliny Azevedo; Avena, Katia de Miranda (São Paulo Medical Journal, 2025)
BACKGROUND: Studies have indicated a substantial increase in alcohol consumption among university students. Specifically, abusive consumption among health students can adversely affect their academic training and future professional practice. OBJECTIVE: This study aimed to analyze alcohol consumption habits among healthcare students and investigate the associations between alcohol consumption patterns and sociodemographic and academic variables. DESIGN AND SETTING: We performed this cross-sectional study at a private university located in the city of Salvador, Bahia. METHODS: We conducted this study with 770 students using a printed, self-administered, anonymous questionnaire containing sociodemographic and academic performance data, as well as the Alcohol Use Disorders Identification Test (AUDIT) and Rutgers Alcohol Problems Inventory (RAPI). RESULTS: We observed that the prevalence of alcohol consumption (65.1%) and binge drinking (57.5%) among Brazilian healthcare students was high, with more frequent consumption among men (73.1%), in medicine (83.0%) and veterinary medicine (79.1%) programs and in semesters beyond the fourth (71.7%). We found associations between drinking habits and sex (P = 0.016), religion (P < 0.000), course (P < 0.000) and semester (P = 0.047). Binge drinking was associated with attending academic activities without getting any sleep (P < 0.000), missing classes due to hangovers (P < 0.000), encountering issues with the institution’s administration (P = 0.028), and failing to complete activities due to alcohol consumption (P < 0.000). CONCLUSION: The prevalence of alcohol consumption and binge drinking among Brazilian healthcare students was high and associated with sex, religion, course, academic semester, risky behaviors, and negative academic impacts.